Distinct Contributions of Median Raphe Nucleus to Contextual Fear Conditioning and Fear-Potentiated Startle - Silva, R. C. B. (Hindawi Publishing Corporation, 2002)
Ascending 5-HT projections from the median raphe nucleus (MRN), probably to the hippocampus, are implicated in the acquisition of contextual fear (background stimuli), as assessed by freezing behavior. Foreground cues like light, used as a conditioned stimulus (CS) in classical fear conditioning, also cause freezing through thalamic transmission to the amygdala. As the MRN projects to the hippocampus and amygdala, the role of this raphe nucleus in fear conditioning to explicit cues remains to be explained. Here we analyzed the behavior of rats with MRN electrolytic lesions in a contextual conditioning situation and in a fear-potentiated startle procedure. The animals received MRN electrolytic lesions either before or on the day after two consecutive training sessions in which they were submitted to 10 conditioning trials, each in an experimental chamber (same context) where they. received foot-shocks (0.6 mA, 1 sec) paired to a 4-sec light CS. Seven to ten days later, the animals were submitted to testing sessions for assessing conditioned fear when they were placed for five shocks, and the duration of contextual freezing was recorded. The animals were then submitted to a fear-potentiated startle in response to a 4-sec light-CS, followed by white noise (100 dB, 50 ms). Control rats (sham) tested in the same context showed more freezing than did rats with pre- or post-training MRN lesions. Startle was clearly potentiated in the presence of light CS in the sham-lesioned animals. Whereas pretraining lesions reduced both freezing and fear-potentiated startle, the post-training lesions reduced only freezing to context, without changing the fear-potentiated startle. In a second experiment, neurotoxic lesions of the MRN with local injections of N-methyl-D-aspartate or the activation of 5-HT(1A) somatodendritic auto-receptors of the MRN by microinjections of the 5-HT(1A) receptor agonist 8-hydroxy- 2-(di-n-propylamino)tetralin (8-OH-DPAT) before the training sessions also reduced the amount of freezing and the fear-potentiated startle. Freezing is a prominent response of contextual fear conditioning, but does not seem to be crucial for the enhancement of the startle reflex by explicit aversive cues. As fear-potentiated startle may be produced in posttraining lesioned rats that are unable to freeze to fear contextual stimuli, dissociable systems seem to be recruited in each condition. Thus, contextual fear and fear-potentiated startle are conveyed by distinct 5-HT-mediated circuits of the MRN.